2023
DOI: 10.1055/s-0042-1760675
|View full text |Cite
|
Sign up to set email alerts
|

Preparing the Bowel (Microbiome) for Surgery: Surgical Bioresilience

Abstract: The preparation of the bowel for radical surgery is a corner stone of elective colorectal practice. The evidence for this intervention is of variable quality and it is often contradictory, yet there is now a global move toward the adoption of oral antibiotic therapy for the reduction of perioperative infective complications, such as surgical site infections. The gut microbiome is a critical mediator of the systemic inflammatory response to surgical injury, wound healing, and perioperative gut function. The los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…The current body of clinical evidence regarding the effect of bowel preparation on the microbiome in colorectal surgery is expanding. However, conflicting results have hindered the formation of a clear consensus on targeted interventions for patient care [94]. Another challenge in detecting the effect of microbiome changes on patient outcomes arises from the overall low event rates of complications such as anastomotic leaks and surgical site infections in colorectal surgery.…”
Section: Clinical Implications and Areas Of Future Studymentioning
confidence: 99%
“…The current body of clinical evidence regarding the effect of bowel preparation on the microbiome in colorectal surgery is expanding. However, conflicting results have hindered the formation of a clear consensus on targeted interventions for patient care [94]. Another challenge in detecting the effect of microbiome changes on patient outcomes arises from the overall low event rates of complications such as anastomotic leaks and surgical site infections in colorectal surgery.…”
Section: Clinical Implications and Areas Of Future Studymentioning
confidence: 99%
“…An interesting new term is 'surgical bioresilience', which describes the concept of optimizing the gut microbiota before surgery, by encouraging microbial diversity. 11 A recent systematic review and meta-analysis from our group found that perioperative probiotics/synbiotics were associated with a significant reduction in postoperative infections following elective colorectal resection (RR 0.55, 95% CI 0.14 to 0.74, P < 0.0001). 12 However, we found major heterogeneity in perioperative regimens among included randomized controlled trials (RCTs).…”
mentioning
confidence: 95%
“…Postoperative infections include SSIs as well as non‐SSIs such as pneumonia or urinary tract infections. An interesting new term is ‘surgical bioresilience’, which describes the concept of optimizing the gut microbiota before surgery, by encouraging microbial diversity 11 …”
mentioning
confidence: 99%